The Correlation between Students’ Grammar Proficiency and Speaking Fluency: A Study in English Education Study Program - Patty, Jusak; Lekatompessy, Felicia; Yudha, Muhammad (Pattimura Excellence Journal of Language and Culture, 2023)
Speaking as the part of four main skills in English can be considered as the most demanding yet the most difficult skill to be mastered. Thus, several ways to master speaking have been researched by experts, one of which is in terms of fluency. As fluency tends to focus on students' ability to speak fluently, subtly, and spontaneously, the grammar aspect is rarely considered as one of the aspects that is related to fluency because grammar is closely related to accuracy. Concerning the aforementioned fact, the objective of this case was to examine the correlation between English grammar proficiency and speaking fluency. The researcher used quantitative method and correlation research design. The population was 103 of 2021 batch students, at English Education Study Program of Pattimura University of which the sample was 31 students from class A. The instruments were in the form of grammar written test and speaking oral test. The student’s grammar proficiency scores (X) and the student’s speaking fluency (Y) were analyzed and it is found that the distribution of data was normal and linear. The result of data analysis showed that the significant value was at 0.001 and the correlation coefficient was at 0.853. The interpretation of the relationship is positive correlation and the strength of correlation is perfect. Consequently, the alternative hypothesis (Ha) is accepted which indicates positive and significant correlation between students’ grammar proficiency and their speaking fluency. These findings suggest that it is important for students to increase their grammar proficiency level in order to improve their speaking fluency.